Talbot laser for Airy pulse generation - M Cuenca; H Maestre; C R Fernández-Pousa (JPhys Photonics)
We report a C-band fiber Talbot laser—an injection-seeded frequency-shifting active ring cavity operated above threshold—emitting trains of far-field Airy pulses characterized by a dominant cubic spectral phase. Pulses are created by the coherent addition of the recirculating seed wavelength under a large roundtrip first-order dispersion. Single-sided Airy pulse trains with sub-ns pulse widths, 80 MHz repetition rate, and bandwidth exceeding 10 GHz are generated at both integer and fractional Talbot conditions. At detuned Talbot conditions pulses are shown to be tailorable by recirculation-induced first-order dispersion. The far-field character of the resulting waveforms is demonstrated, and the performance in terms of amplitude noise and timing jitter, in this last case after the introduction of active loop stabilization, is evaluated.